Foetal Haemoglobin as a Marker of Bone Marrow Suppression Secondary to Anti-Kell Alloimmunisation - Rodrigo Alfredo Morales Painamil; José Manuel González de Aledo-Castillo; Marta Teresa-Palacio; Ana Argudo-Ramírez; Rosa M. López-Galera; Abraham J. Paredes-Fuentes; Victoria Aldecoa-Bilbao; Miguel Alsina-Casanova (MDPI AG, 2023)
Anti-Kell alloimmunisation is a potentially severe minor blood group type incompatibility, not only as a cause of haemolytic disease of the foetus and newborn, but also due to the destruction of red blood cells (RBC) and mature form in the bone marrow with the subsequent hyporegenerative anaemia. In severe cases and when the foetus shows signs of anaemia, an intrauterine transfusion (IUT) may be necessary. When repeated, this treatment can suppress erythropoiesis and worsen the anaemia. We report the case of a newborn who required four IUTs plus an additional RBC transfusion at one month of life due to late onset anaemia. The identification of an adult haemoglobin profile with a complete absence of foetal haemoglobin in the patient's newborn screening samples at 2 and 10 days of life warned us of a possible late anaemia. The newborn was successfully treated with transfusion, oral supplements and subcutaneous erythropoietin. A blood sample taken at 4 months of life showed the expected haemoglobin profile for that age with a foetal haemoglobin of 17.7%. This case illustrates the importance of a close follow-up of these patients, as well as the usefulness of the haemoglobin profile screening as a tool for anaemia assessment.